Abandoned Remšnik mine with ramsbeckite and namuwite(?) - Trajanova, Mirka; Žorž, Zmago (Geologija, 2013)
The polymetallic Remšnik ore deposit is situated at the Kobansko area in northern Slovenia. Mineralization occurs in the thrust zone of the weakly metamorphosed old Palaeozoic rocks of the Magdalensberg formation, the Remšnik nappe, onto the retrogressed schists of the Austroalpine metamorphic basement. Hydrothermal ore mineralization and silicification follow slaty cleavage in partly brecciated marmorized dolomite lenses and subordinately in metatuffites and phyllites. Its origin is most probably connected to the lively Tertiary magmatism, occurring at the Pohorje Mountains. Mineral paragenesis of the predominant Pb, Cu and Zn silver bearing sulphide ore is associated with numerous secondary minerals. Among them, two rare sulphates with H2O of Cu and Zn occur, found for the first time in Slovenia. The green, transparent monoclinic crystals, only some tenth of millimetre in size were determined by SEM as ramsbeckite (Cu, Zn)15(SO4)4(OH)22 ∙ 6(H2O). Greenish in colour are also leafy, hexagonal, flowery intergrown crystals, which most probably belong to namuwite (Cu, Zn)4(SO4)(OH)6 ∙ 4(H2O). Its submicroscopic size and small quantity did not permit reliable determination, yet.